Effect of cold stimulation on myocardial perfusion. An investigation using thallium-201 scintigraphy. Issue 1 (July 1984) - Rodger, J C; Railton, R; Parekh, P; Newman, P
Abstract : Thallium-201 scintigraphy was used to investigate the effects of cold stimulation on myocardial perfusion in 12 patients with documented coronary artery disease (group 1), nine with chest pain but without evidence of structural coronary artery disease (group 2), and 10 normal volunteers (group 3). The scintigrams were assessed both visually and numerically using a circumferential profile technique. Transient perfusion defects were identified by both techniques in six subjects in group 1, three in group 2, and two in group 3. The haemodynamic responses (assessed by the double product) of subjects with or without transient perfusion defects were not significantly different. Thus cold stimulation can provoke abnormalities of myocardial perfusion not only in patients with coronary heart disease but also in those with structurally normal coronary arteries and in some normal subjects. These results may reflect a spectrum of coronary vasomotor responsiveness to cold stimulation in both normal and ischaemic populations, and it is concluded that cold pressor techniques cannot be relied on to differentiate patients with coronary heart disease from those with atypical chest pain syndromes or even from normal subjects.